1993
DOI: 10.1111/j.1365-2958.1993.tb00911.x
|View full text |Cite
|
Sign up to set email alerts
|

Isogenic P‐fimbrial deletion mutants of pyelonephritogenic Escherichia coli: the role of α Gal(1–4)β Gal binding in virulence of a wild‐type strain

Abstract: Escherichia coli strains causing acute pyelonephritis often express multiple fimbrial types and haemolysin, which may contribute to their ability to adhere to, and interact with, kidney epithelial cells. Strain CFT073, a pap+, sfa+, pil+, hly+ pyelonephritis strain, previously established as virulent in the CBA mouse model of ascending urinary tract infection and cytotoxic for cultured human renal epithelial cells, was selected for construction of isogenic strains. From a gene bank of this strain, two distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
150
1
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(153 citation statements)
references
References 45 publications
1
150
1
1
Order By: Relevance
“…Introduction of genetic lesions affecting P pili to E. coli HU734 (Hagberg et al, 1983b) and E. coli DS17 (Roberts et al, 1994) reduced their virulence as indicated by the murine and primate models, respectively. Although these and other data clearly establish an important role for P pili as virulence determinants in pyelonephritis, the elimination of P pili did not reduce the virulence of pyelonephritis isolate CFT073 as determined by the murine model (Mobley et al, 1993). These and other observations suggest that E. coli CFT073 is more virulent than E. coli HU734 (Mobley et al, 1993).…”
Section: Systemmentioning
confidence: 54%
“…Introduction of genetic lesions affecting P pili to E. coli HU734 (Hagberg et al, 1983b) and E. coli DS17 (Roberts et al, 1994) reduced their virulence as indicated by the murine and primate models, respectively. Although these and other data clearly establish an important role for P pili as virulence determinants in pyelonephritis, the elimination of P pili did not reduce the virulence of pyelonephritis isolate CFT073 as determined by the murine model (Mobley et al, 1993). These and other observations suggest that E. coli CFT073 is more virulent than E. coli HU734 (Mobley et al, 1993).…”
Section: Systemmentioning
confidence: 54%
“…Among the functional similarities, the finding that type 1 pili are expressed in the early steps of avian colibacillosis and that P pili are expressed in the later steps is reminiscent of the finding that the UPEC strain J96 expresses either type 1 pili or P-pili, but not both at the same time, the expression of type 1 pili being inhibited by the PapB protein (Mobley et al, 1993;Pourbakhsh et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Virulence determinants common to APEC and ExPEC have been identified. They include the aerobactin iron transport system, the K1 capsule and type 1 and P fimbriae (Bahrani-Mougeot et al, 2002;Dho-Moulin & Fairbrother, 1999;Gunther et al, 2002;Hoffman et al, 1999;Mobley et al, 1993;Pourbakhsh et al, 1997;Torres et al, 2001). Vandemaele and colleagues also found a high level of homology between papG sequences, the P pilus adhesin gene from APEC isolates and papG sequences from mammalian E. coli isolates, including human isolates (Vandemaele et al, 2003;Johnson et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Motility was measured 18 h after inoculation to Luria-Bertani motility (0.4% agar) plates. Suicide vector pCVD442 (pir-dependent replicon, Amp R , sacB gene conferring sucrose sensitivity) was used to replace the WT fliC allele on the chromosome as described previously (45). Briefly, plasmid pCVD442 carrying a mutant fliC allele was transferred to FljB-null SL1344 (BC687) by conjugation, and the resulting Amp R Salmonella were then grown in sucrose-containing medium to select for loss of sacB gene and plasmid DNA.…”
Section: Generation Of Salmonella Flic Export Mutantsmentioning
confidence: 99%